Peran Kepemimpinan Kepala Sekolah Di MTS Al-Jihad Kota Medan - Aulia Jannah; Nurul Adinda Lubis; Shakila Putri Suhara; Afrizal Rambe; Inom Nasution (Pusat Riset dan Inovasi Nasional, 2023)
This research discusses the role of leadership at MTs Al-Jihad Medan City. The role of leadership is key where a leader is very influential and has a big impact in advancing, developing and making the madrasa institution successful in achieving its stated goals. Leaders have the responsibility and carry out a large mandate to guide and lead the continuity of all activity processes in the agency so that they run smoothly and in accordance with the plans that have been prepared as well as possible. This research uses qualitative research which is descriptive in nature and tends to prioritize analysis. The theoretical basis is used as a guide so that the research focus is in accordance with the facts in the field.